Variability of the lymphocyte-to-monocyte ratio in patients with chronic kidney disease on hemodialysis - Daysi Zulema Diaz-Obregón; Gabriela Goyoneche Linares; Ana Granda Alacote; Alexis G. Murillo Carrasco; Michael Bryant Castro Núñez; Andrea Vanessa Llanos Diaz; Katherine Susan Rufasto Goche; Antonio Mauricio Sánchez Cotrina; Víctor Arrunátegui Correa; Joel de León Delgado (PLoS ONE, 2025)
Introduction Chronic kidney disease (CKD) is a global public health issue characterized by a state of persistent inflammation that leads to immune system dysregulation. The lymphocyte-to-monocyte ratio (LMR) has emerged as an inflammatory biomarker of interest for monitoring the progression of this condition. Objective To determine the clinical-epidemiological, biochemical, and hematological characteristics associated with differences in the LMR in patients with chronic kidney disease undergoing hemodialysis. Materials and Methods A retrospective cohort study was conducted by reviewing the medical records of 120 CKD patients on hemodialysis treated at a private nephrology center in Lima, Peru. Patients were divided into two groups based on the median LMR value: high LMR (< 3.06) and low LMR (≥ 3.06). Logistic regression was used to analyze risk factors associated with LMR variation, complemented by longitudinal regression analysis (up to three years follow-up). Results The median age of the patients was 58 years at the time of analysis. Chronic glomerulonephritis, arterial hypertension, and type 2 diabetes mellitus (T2DM) were the most frequently reported causes of end-stage CKD. A total of 54.2% of patients had been on hemodialysis for more than seven years. Risk factors associated with decreased LMR, and thus with increased inflammation, were: older age (OR = 1.03, p < 0.001), more than three years on hemodialysis (OR = 2.17, p = 0.002), more than seven years on hemodialysis (OR = 2.38, p < 0.001), and presence of T2DM (OR = 2.2, p = 0.006). In addition, a direct positive contribution was found with hematocrit levels (Beta = 0.25, p < 0.001) and the presence of an arteriovenous fistula (Beta = 0.17, p = 0.038). Conclusions A reduced LMR is a useful inflammatory biomarker for monitoring CKD severity. Increased age, prolonged duration of hemodialysis (more than three years), presence of T2DM, and elevated ferritin levels are associated with lower LMR values. In contrast, higher hematocrit levels and the presence of an arteriovenous fistula are directly associated with higher LMR values.